How COVID-19 impacted soft skills development: The views of software engineering students - Attracta Brennan; Mary Dempsey; John McAvoy; Majella O’Dea; Sharon O’Leary; Margaret Prendergast (Cogent Education, 2023)
AbstractSince a pandemic was declared in 2020, Irish higher education institutions transitioned from on-campus to online delivery. This disruption created challenges to students’ acquisition of hard and soft skills. With greater employee mobility, there is an increased emphasis on soft skills development, especially those skills that enhance employability, i.e., creativity, leadership, communication, innovation, teamwork, adaptability, resilience, time management, organization, self motivation, ability to work under pressure, critical thinking and problem solving and organizational ability. The purpose of this study was to understand the effects of COVID-19 on fears for the future and on soft skills development. In this study, 111 Software Engineering university students were surveyed. The results show heightened fears for the future with regard to job opportunities, the loss of time and the lack of control. While females reported to being more fearful, they also reported enhanced empathy and strengthened resilience. Postgraduate students were less fearful about the future compared to undergraduate students whilst also reporting better time management and organization skills. This study showed that despite disruptions to education, the Software Engineering students self-reported enhancements to resilience, empathy, time management and organizational skills, with the greatest impact on resilience and time management.